STRUKTUR DAN SISTEM ORGANISASI PENDIDIKAN ISLAM YANG DINAMIS - Romzi, Moh; Ansori, Ansori; Noviyanti, Shobihatul Fitroh; Salas, Mohamad kamil (Ma'arif Journal of Education, Madrasah Innovation and Aswaja Studies, 2024)
This study aims to examine organizational structure from various perspectives, with a specific focus on Islamic education, through a literature review approach. The definition of organizational structure encompasses the division of work, determination of authority, and relationships among individuals within the organization, as discussed by various experts. Key elements addressed include work specialization, departmentalization, chain of command, span of control, centralization and decentralization, and formalization. The study also identifies differences in organizational structures, particularly between mechanistic models, which are formal and bureaucratic, and organic models, which are more flexible and participative. Types of organizational structures reviewed include line, line and staff, functional, line and functional, matrix, and committee organizations. Additionally, this research highlights the importance of developing organizational structures in response to changes in business strategies, company growth, and external regulations. The findings indicate that adapting organizational structures to environmental changes and operational needs is crucial for enhancing organizational effectiveness and efficiency. Using the literature review method, this study concludes that an adaptive and integrative approach to managing organizational structures, especially in the context of Islamic education, can positively contribute to achieving organizational goals and improving management quality.